Syllable awareness and phonological skills of preschool and kindergarten Filipino children - Tan, Anne Sheila K. (2007)
Phonological skills are found to be crucial for early literacy training. This study investigated the effects of a syllable awareness training program on 26 Preschool (3-4 years old) and 25 Kindergarten (5-6 years old) Filipino children. It also focused on the relationship of syllable awareness to other levels of phonological awareness, as well as the difference in the time preschoolers and kindergarteners need to master syllable awareness skills to criterion. A phonological awareness battery was created and administered to the participants. It was shown that in a span of about one month from pretest to posttest, the groups have improved their syllable awareness skills. The rhyme awareness and phonemic awareness skills of the children hardly showed any change. Data from the study also confirmed that the length of training also affects the development of syllable awareness skills.
"March 2007."
Thesis (M.A. Reading Education)--University of the Philippines, Diliman.
Keywords: Language arts (Preschool) -- Philippines -- Quezon City; Language arts (Kindergartenl) -- Philippines -- Quezon City; Phonetics -- Study and teaching (Preschool) -- Philippines -- Quezon City; Phonetics -- Study and teaching (Kindergarten) -- Philippines -- Quezon City; Language awareness in children; Reading -- Phonetic method